2010
DOI: 10.3141/2145-02
|View full text |Cite
|
Sign up to set email alerts
|

Bus Network Planning for Transfers and the Network Effect in Melbourne, Australia

Abstract: Although passengers dislike transferring, efficient transit systems should facilitate transfers to provide auto-competitive citywide access. This paper reviews bus transfer behavior in Melbourne, Australia, to understand causal factors. It also explores network effects: high ridership associated with frequent services or simple (grid) networks or both. Half of bus users make transfers, mostly to rail. The number of tram and bus transfers is generally low; however, in inner and central business district areas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The survey sample was drawn from a diverse population of commuters travelling by urban bus and metro in the city of Madrid. In common with other researches [8,16], the survey was restricted to commuters due to their higher transfer rates [17]. This research considers commuters to be people who periodically and recurrently travel between their place of residence and their place of work or study.…”
Section: Introductionmentioning
confidence: 99%
“…The survey sample was drawn from a diverse population of commuters travelling by urban bus and metro in the city of Madrid. In common with other researches [8,16], the survey was restricted to commuters due to their higher transfer rates [17]. This research considers commuters to be people who periodically and recurrently travel between their place of residence and their place of work or study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Guo and Wilson 2004;Ceder et al 2009) have shown that commuters are only willing to tolerate the inconvenience caused by transfers if the perceived benefits of selecting a route with transfers are greater than the direct route. A number of studies (Liu et al 1997;Vande Walle and Steenberghen 2006;Bamberg et al 2007;Beirao and Sarsfield-Cabral 2007;Guo and Wilson 2007;Iseki and Taylor 2009;Currie and Loader 2010;Guo and Wilson 2011;Sharaby and Shiftan 2012) have been conducted to identify the operational and psychological factors that dictate the inconvenience felt by transit users when undertaking routes with transfers. These studies have indicated the importance of including transfers in the planning stage of an integrated transport system.…”
Section: Introductionmentioning
confidence: 99%
“…Currie and Loader (2010) reviewed bus transfer behaviour, identifying half of bus users make transfers, mostly to rail. Currie and Loader conclude that high transfer volumes occur where at least one route has a frequency of 10 min or better, but conclusive proof of the network effect remains elusive.…”
Section: Network Planning Principles and Increasing Patronagementioning
confidence: 99%